IMPLEMENTATION OF EPIGENETIC PRINCIPLE IN THE CONTENTS OF PERSONALITY OF PEOPLE WITH MENTAL DISABILITIES - Buls, Aivars (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2016)
The aim of this qualitative research was to determine the typical of the contents of personality of grown-up people with mental disabilities as well as when and under what conditions that became typical of them. 22 people of both genders aged between 22 and 58 took part in this study, all of them have 2nd group of mental or both mental and physical disabilities and live in Social Care home on regular and stable basis (>5 years). Research took part in the context of their living environment, both during everyday life using method of Symbolic interactionism, and retrospectively according to the human development model epigenetic insights. To describe the contents of personality the typological approach was used. Results of this study show that personological problems of these people that weren’t identified and treated in a timely manner in most cases intensify and are transferred in the coming ages under conditions of destructive living environment.